2005
DOI: 10.1038/nature03906
|View full text |Cite
|
Sign up to set email alerts
|

Increasing destructiveness of tropical cyclones over the past 30 years

Abstract: Theory and modelling predict that hurricane intensity should increase with increasing global mean temperatures, but work on the detection of trends in hurricane activity has focused mostly on their frequency and shows no trend. Here I define an index of the potential destructiveness of hurricanes based on the total dissipation of power, integrated over the lifetime of the cyclone, and show that this index has increased markedly since the mid-1970s. This trend is due to both longer storm lifetimes and greater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
2,292
13
34

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,295 publications
(2,417 citation statements)
references
References 21 publications
78
2,292
13
34
Order By: Relevance
“…Numerical modeling of late 21 st century hurricane climatology has suggested that declines in overall Atlantic hurricane frequency could occur simultaneously with a broadening of the intensity distribution of hurricanes leading to fewer but more intense storms , Gualdi et al 2008, Knutson et al 2008, Zhao et al 2009, Bender et al 2010). However, recent warming and increased hurricane frequency in the Atlantic has purportedly been accompanied by a disproportionate increase in the occurrence of intense hurricanes (Emanuel 2005, Webster et al 2005, Hoyos et al 2006. When considering the climate system feedbacks likely associated with the atmospheric and upper ocean anomalies generated by tropical cyclones (Hart et al 2007, Hart 2010, it seems likely that significant changes in the frequency of storms would also change their intensity statistics.…”
Section: Comparisons With Other Paleohurricane Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical modeling of late 21 st century hurricane climatology has suggested that declines in overall Atlantic hurricane frequency could occur simultaneously with a broadening of the intensity distribution of hurricanes leading to fewer but more intense storms , Gualdi et al 2008, Knutson et al 2008, Zhao et al 2009, Bender et al 2010). However, recent warming and increased hurricane frequency in the Atlantic has purportedly been accompanied by a disproportionate increase in the occurrence of intense hurricanes (Emanuel 2005, Webster et al 2005, Hoyos et al 2006. When considering the climate system feedbacks likely associated with the atmospheric and upper ocean anomalies generated by tropical cyclones (Hart et al 2007, Hart 2010, it seems likely that significant changes in the frequency of storms would also change their intensity statistics.…”
Section: Comparisons With Other Paleohurricane Recordsmentioning
confidence: 99%
“…Meteorological records of the number, track and intensity of hurricanes in the Atlantic extend back to the mid-19 th century, although debate exists over whether trends in storm observations genuinely reflect secular changes in the underlying population of Atlantic hurricanes or if advances in storm detection and observation prevent the attribution of these trends to changes in storm climate (Goldenberg et al 2001, Emanuel 2005, Webster et al 2005, Anthes et al 2006, Hoyos et al 2006, Mann and Emanuel 2006, Trenberth and Shea 2006, Chang and Guo 2007, Kossin et al 2007, Landsea 2007, Mann et al 2007, Chen et al 2009). Moreover, the brief observational record is inadequate for characterizing natural variability in hurricane activity occurring on longer than multi-decadal timescales.…”
Section: Review and Motivationmentioning
confidence: 99%
“…Most of the societal impacts of these events are perceived negatively, as both TCs and droughts often impose high economic costs. Specifically, land-falling TCs are associated with loss of human life, coastal property damage, and inland flooding from extreme precipitation events (Lyons 2004;Emanuel 2005;Crossett et al 2008;Pompe and Rinehart 2008). Persistent droughts in the southeastern United States can have severe economic impacts, particularly in the form of agricultural losses (Morehart et al 1999;Ortegren et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar uncertainty exists in identifying cyclolysis. These uncertainties can project onto metrics such as power dissipation 10 and accumulated cyclone energy 11 , which are amalgamations of frequency, duration, and intensity.…”
mentioning
confidence: 99%